Subtle Variations of the Electronic Structure and Mechanical Properties of High Entropy Alloys With 50% Carbon Composites - San, Saro; Ching, Wai-Yim (Frontiers in Materials, 2020)
Binary and ternary transition metal carbides are stable ceramic crystals with outstanding mechanical properties. In recent years, multi-component single-phase high entropy alloys (HEAs) enjoyed explosive growth due to many of their outstanding physical properties with its large and flexible composition space. Hence the composite between them can be advantageous in forming a new class of ceramic materials with combined superiority in their properties for many applications. On the basis of a systematic large-scale ab initio simulations using density functional theory that are specifically designed for their compositional variations, subtle differences in their structures, electronic and mechanical properties are revealed and discussed in detail. Fifteen supercell models with 512 atoms with equal composition of C and HEAs occupying the sub-lattices of the rock-slat structure were constructed. These models are fully optimized, and their properties carefully characterized, compared and contrasted. By applying the novel concept of total bond order density and its partial components, the partial bond order density, we revealed many subtle variations in their properties that have not been known before. This large database can play an important and valuable role in the design and synthesis of high entropy ceramic carbides.